The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/fi12100172
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Resource Scheduling Strategy for V2X Microservice Deployment in Edge Servers

Abstract: The fast development of connected vehicles with support for various V2X (vehicle-to-everything) applications carries high demand for quality of edge services, which concerns microservice deployment and edge computing. We herein propose an efficient resource scheduling strategy to containerize microservice deployment for better performance. Firstly, we quantify three crucial factors (resource utilization, resource utilization balancing, and microservice dependencies) in resource scheduling. Then, we propose a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…In their work [18], the authors proposed an efficient resource scheduling strategy to optimize the deployment of V2X (Vehicle-to-Everything) microservices in edge servers. They addressed the challenge of resource allocation in edge computing environments by introducing a dynamic resource allocation algorithm that took into consideration service requirements and resource availability.…”
Section: Big Data Simulatorsmentioning
confidence: 99%
“…In their work [18], the authors proposed an efficient resource scheduling strategy to optimize the deployment of V2X (Vehicle-to-Everything) microservices in edge servers. They addressed the challenge of resource allocation in edge computing environments by introducing a dynamic resource allocation algorithm that took into consideration service requirements and resource availability.…”
Section: Big Data Simulatorsmentioning
confidence: 99%
“…Other researchers [10] suggest a model for multi-objective resource scheduling for vehicle-to-everything (V2X) microservices based on the edge container cloud architecture. The scheduling model that the authors worked on is the multiple fitness genetic algorithm (MFGA).…”
Section: π‘šπ‘’π‘š_𝑒𝑑𝑖𝑙(𝑛mentioning
confidence: 99%
“…Using those three factors, the authors introduced the goal of this study under the formula of an objective function, as shown in equation (10).…”
Section: π‘šπ‘’π‘š_𝑒𝑑𝑖𝑙(𝑛mentioning
confidence: 99%
See 2 more Smart Citations